2012
DOI: 10.1111/j.1742-9544.2011.00052.x
|View full text |Cite
|
Sign up to set email alerts
|

The Geriatric Anxiety Inventory: International Use and Future Directions

Abstract: Anxiety in later life is relatively common in older populations but remains under-diagnosed and treated. Both primary and comorbid anxiety disorders in later life contribute to overall burden of disease, which is reflected in excess morbidity and mortality. One important means to reduce excess burden and instigate appropriate treatments for older adults with anxiety is to accurately assess this condition more across diagnoses and settings. The introduction of the Geriatric Anxiety Inventory and its variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 40 publications
1
21
0
3
Order By: Relevance
“…A reliability generalisation metaanalysis confirmed that the GAI is appropriate for assessing anxiety in older adults (Therrien and Hunsley 2013), and alphas were acceptable for the current study at both preintervention (a = .89) and follow-up (a = .95). As a cutoff of 8/9 is recommended to detect clinically-significant anxiety (Byrne et al 2010;Pachana and Byrne 2012), the mean baseline score was not in the clinical range (M = 4.23, SD = 5.72, range 0-20).…”
Section: Methodsmentioning
confidence: 99%
“…A reliability generalisation metaanalysis confirmed that the GAI is appropriate for assessing anxiety in older adults (Therrien and Hunsley 2013), and alphas were acceptable for the current study at both preintervention (a = .89) and follow-up (a = .95). As a cutoff of 8/9 is recommended to detect clinically-significant anxiety (Byrne et al 2010;Pachana and Byrne 2012), the mean baseline score was not in the clinical range (M = 4.23, SD = 5.72, range 0-20).…”
Section: Methodsmentioning
confidence: 99%
“…We chose to obtain data using structured interviews. The scoring is based on symptoms during the previous week [31]. Each item can be scored as 0 (symptom not present) or 1 (symptom present); thus, the total score can range from 0 to 20; a higher score denotes more severe anxiety [30].…”
Section: Methodsmentioning
confidence: 99%
“…It can be used as a self-reporting instrument or as a structured interview, and it is used to rate the severity of anxiety and to detect general anxiety disorder. The scoring is based on symptoms during the previous week [25]. In the present study, the patients were interviewed.…”
Section: Methodsmentioning
confidence: 99%